2008
DOI: 10.1590/s0104-11692008000600004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the nature of spiritual pain in terminal patients and the resignification process through the relaxation, mental images and spirituality (RIME) intervention

Abstract: Elias ACA, Giglio JS, Pimenta CAM. Analysis of the nature of spiritual pain in terminal patients and the resignification process through the Relaxation, Mental Images and Spirituality (RIME) Intervention. Rev Latinoam Enfermagem 2008 novembro-dezembro; 16(6) ANÁLISIS DE LA NATURALEZA DEL DOLOR ESPIRITUAL PRESENTADO POR PACIENTES TERMINALES Y EL PROCESO DE ELABORACIÓN DE UN NUEVO SIGNIFICADO A TRAVÉS DE LA INTERVENCIÓN DE RELAJAMIENTO, IMÁGENES MENTALES Y ESPIRITUALIDAD (RIME)Objetivo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
11

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 8 publications
1
11
0
11
Order By: Relevance
“…The categories were developed based on Analytical Psychology 12-16 , for the symbolic interpretation of the data, with the processing of the data performed through thematic content analysis [6][7][8] This study aimed to promote socio-psycho-spiritual transformations through RIME, focusing on the transformation of the psychological distress chosen by the patient, not necessarily related to breast cancer, in order to contribute to the quality of life and self-esteem and to minimize the hopelessness of these patients. Comparing the RIME intervention with the BP applied with the Control Group, considering the statistical analysis, it was observed that the RIME had more strength in psychic structuring and ego strengthening than the BP, even though both caused a significant improvement in the perceived quality of life and self-esteem of the patients.…”
Section: -Qualitative Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The categories were developed based on Analytical Psychology 12-16 , for the symbolic interpretation of the data, with the processing of the data performed through thematic content analysis [6][7][8] This study aimed to promote socio-psycho-spiritual transformations through RIME, focusing on the transformation of the psychological distress chosen by the patient, not necessarily related to breast cancer, in order to contribute to the quality of life and self-esteem and to minimize the hopelessness of these patients. Comparing the RIME intervention with the BP applied with the Control Group, considering the statistical analysis, it was observed that the RIME had more strength in psychic structuring and ego strengthening than the BP, even though both caused a significant improvement in the perceived quality of life and self-esteem of the patients.…”
Section: -Qualitative Resultsmentioning
confidence: 99%
“…A qualitative approach was based on Analytical Psychology 12-16 , for the symbolic interpretation of the data, with the processing of the data performed through thematic content analysis [6][7][8] Fisher's exact test and Welch's t test, showing no significant differences, i.e., p values greater than 0.05, as shown in Table 1.…”
Section: This Study Was Approved Without Restrictions By the Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The SPIRIT-6 intervention included topics such as the meaning and importance of spirituality and religion, the expression of spirituality to others, creative expression of spirituality, forgiveness, and spiritual awareness (Tuck et al, 2006). In contrast, some intervention programs focus on one or more spiritual techniques such as meditation (Elias, Giglio, & Pimenta, 2008), repetitive mantras (Bormann et al, 2006), and prayer (Rajagopal et al, 2002). In a study by Bormann et al (2006), frequent repetition of a mantra (words with spiritual significance) greatly improved stress, trait anxiety, trait anger, quality of life, and spiritual well-being in healthcare workers (Bormann et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The health professionals showed improved coping skills in their personal grief and psycho-spiritual growth, both professionally and personally. Relevant information is that this technique (RIME) is directed to patients who believe in life after death (8)(9) .…”
Section: Introductionmentioning
confidence: 99%